Analisis Dan Optimalisasi Stok Barang di Toko Acc RPH Dengan Metode Program Linear - Nasution, Adinda Ayu; Rambe, Ulfa Ufrona; Harahap, Ayu Sari; Sartika, Tiara; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
Competition in the business world is becoming increasingly complex, especially in the rapidly growing mobile accessories industry. This study aims to analyze and optimize inventory management at Toko Acc RPH using the linear programming method. By considering market demand, production capacity, and profitability, this research applies the simplex method in linear programming to determine the optimal quantity of products to be stocked. The data used in this study includes inventory levels, selling prices, production quantities, and store demand. Analysis was conducted using QM for Windows software to obtain optimal stock distribution solutions. The results show that the store's inventory management strategy is efficient, ensuring that customers do not experience stock shortages despite limited inventory levels. Thus, the use of linear programming proves effective in optimizing inventory and improving operational efficiency.